12 Prinsip Animasi Dalam Serial “Adit & Sopo Jarwo” - Wahju Tri Widadijo (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2017)
This article reviews the analysis of the functions and roles of 12 basic principles of animation in the animation produced in Indonesia “Adit & Sopo Jarwo”. This serial produced by MD Animation was released on Januari, 27th, 2014 and broadcasted from a TV station in Indonesia. This film is about the friendships and daily adventures developed in the plots between the main characters, Adit, Dennis, and Sopo Jarwo. This study is based on the initial assumption, that is, one of the indicators of a good animation is how the impression of every movements is created by the animators. To achieve such a good and natural impression of movements, the animators should apply the 12 basic principles of animation, as formulated by Frank Thomas and Ollie Johnston (1981), two former animators of Disney’s. The analytical process itself was using descriptive qualitative method. The purpose of this article is to show the intensity of the using of 12 basic principles of animation in “Adit & Sopo Jarwo”.